The Non-Constant Effect of Defendant Sex across Criminal History: How and When Does Criminal History Condition Sex Disparity at Sentencing? - Holmes, Bryan (Women & criminal justice, 2025)
The goal of this study is to examine how, and when, criminal history conditions the effect of defendant sex on incarceration and prison sentence length decisions in Minnesota state courts. Results suggest that sex differences in sentencing are largely concentrated amongst those who have extensive criminal histories, bypassing those who have little or no criminal history. Moreover, criminal history’s aggravating contextual effect on sex often depends on the dependent variable examined and type of offense committed. Study results shed light on the situations where extralegal disparities are “hidden” in the nuances of case characteristics.